PRODI PENDIDIKAN AGAMA ISLAM DAN MANAJEMEN PENDIDIKAN ISLAM UNIVERSITAS NURUL JADID PAITON PROBOLINGGOO - Afifurrahman, Afifurrahman; Rofayatun, Rofayatun (TA'LIMUNA: Jurnal Pendidikan Islam, 2019)
Curriculum organization is a part of arranging material teaching wich can teach the student or study experience wich want to reach a some purpose such as make student easier in studying material lesson also helping student in doing study activity until me purpose of studying can be reach by affective and optimum. The some procedure in curriculum organizing: studying procedure (book of lesson) procedure to learn other curriculum analisys of adult activity, procedure of social function, opinion survey, wrong studying procedure. Some manner wich should implemented in order education purpose can be reach such as: horizontal stucture is a shape of arranging material teaching for student; vertical structure wich has relation whit system problem, realization, implementation in school. Some component to iplement this curriculum: studying and teaching proces, guidance spread, supervision administration, cullicular means, and rating of student.